Entropy generation of pseudo-plastic non-Newtonian nanofluids in circular duct under constant wall temperature - shabani, mohsen; falahat, alireza; saffarian, mohammadreza (Journal of Mechanical Engineering and Technology (JMET), 2018)
In this paper the second law analysis of thermodynamic irreversibilities in pseudo-plastic non-Newtonian nanofluids through a circular duct under uniform wall temperature thermal boundary have been carried out for laminar flow condition. This nanofluid consists of sodium carboxymethyl cellulose (CMC)–water and two different types of nanoparticles; namely, CuO and Al2O3. Entropy generation is obtained for various Power law number, various volume concentration of nanoparticles, various dimensionless temperature and various Reynolds number. It is found that with the decreasing Power law number and duct length values, total entropy generation at fixed Reynolds number decreases and with increasing wall temperature values, total entropy generation increases, also entropy generation decreases with increasing volume concentration of nanoparticles.